International Student Mobility in a Deglobalizing and Post-Pandemic World: Resilience, Reconfiguration, Renewal - YANG, PEIDONG; TIAN , YI (Journal of International Students, 2023)
Writing about international student mobility (ISM) at such a juncture, there is a certain temptation to go with hyperbolic statements about how the ISM landscape has shifted dramatically in a world characterized by deglobalizing momentum (Irwin, 2020) or how the COVID pandemic was a “game-changer” (Yang & Lu, 2022, p. 133). Undoubtedly, the past several years have been volatile for international students and all those involved in various aspects of ISM. The unsynced trajectories of the pandemic in different regions/countries of the world, aggravated by the pandemic’s multifarious global repercussions – social, economic, geo-political, etc. – have created a cacophony of experiences for international students, about which scholarship is rapidly emerging, both in this journal (to mention just a few: Sustarsic & Zhang, 2021; Thorson et al., 2021; Zabin, 2022) and elsewhere (e.g., Gomes, 2022; Xu & Tran, 2022; Yang, 2022b).